PEMETAAN BERDASARKAN LOKASI DAN JUMLAH PESAING PUSKESMAS PERAWATAN DI KABUPATEN GIANYAR YANG BERSTATUS BLUD SEBAGAI DASAR PENYUSUNAN STRATEGI BISNIS - Indrayathi, Putu Ayu; Hari Mulyawan, Ketut; Novi Trisna Dewi, Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 3 No 1 (2016): Juni (2016), 2016)
Community health care center (Puskesmas) as gate keeper is the first level of health care that is closest to the people. Since January 2010, several puskesmas which provide inpatient care in Kabupaten Gianyar has become public service agencies (BLUD) to improve quality and access to health care services for community During the implementation of such policy, it is important to review its effectiveness especially with so many competitors in the community. This study was a cross-sectional descriptive study. Research carried out in existing health facilities competitors in the work area BLUD community health care centers in Gianyar.  Mapping was conducted using GIS and processed by the Epi Info system. The results showed that the four community health care centers in Gianyar treatments have different levels of competition. Puskesmas Ubud I has a very high density of competition, while Puskesmas Tegallalang II has very little of competition. The implementation of such policy in Puskesmas Payangan and Puskesmas Tegallalang II is considered very effective because far from city and rarely finding a competitor health facilities. This research recommend the community health care center to improve the promotion about existence of health care centers and quality of health care services so that communities in the solid area of competitor can switch utilize community health care center services.
Keywords: GIS, competitor of health care center, inpatient care community health 45 care center BLUD